Supramolecular structure of self-assembled monolayers of ferrocenyl terminated n-alkanethiolates on gold surfaces - Nerngchamnong, Nisachol (Langmuir : the ACS journal of surfaces and colloids, 2014)
It is important to understand the structure of redox-active self-assembled monolayers (SAMs) down to the atomic scale, since these SAMS are widely used as model systems in studies of mechanisms of charge transport or to realize electronic functionality in molecular electronic devices. We studied the supramolecular structure of SAMs of n-alkanethiolates with ferrocenyl (Fc) end groups (S(CH2)nFc, n = 3 or 4) on Au(111) by scanning tunneling microscopy (STM). In this system, the tilt angle of the Fc units with respect to the surface normal (α) depends on the value of n because the Au-S-C bond angle is fixed. The ordered domains of the SAMs were imaged by STM after annealing at 70 °C at ultrahigh vacuum conditions. High resolution electron energy loss spectroscopy (HREELS) and cyclic voltammetry show that this annealing step only removed physisorbed material and did not affect the structure of the SAM. The STM images revealed the presence of row defects at intervals of 4 nm, that is, six molecules. We determined by near edge X-ray absorption fine structure spectroscopy (NEXAFS) that the Fc units of the SAMs of SC3Fc are more parallel to the Au(111) plane with a tilt angle α = 60.2° than the Fc units of SC4Fc SAMs (α = 45.4°). These tilt angles are remarkably close to the tilt angles measured by X-ray diffraction data of bulk crystals (bc-plane). Based on our data, we conclude that the molecules are standing up and the SAMs pack into lattices that are distorted from their bulk crystal structures (because of the build-up stain due to the differences in size between the Fc units and thiolate anchoring groups)